Mechanical properties and durability of ancient mortars in the historic buildings of Eastern Sicily. Issue 3 (14th February 2022) - Anania, Laura; Badalà, Antonio
Abstract: Eastern Sicily's historic buildings are characterized by an almost uniform use of local and naturally available calcareous and lavic stone as aggregate. Also, ancient mortars comprise of lime or cement-lime binder. Very limited studies concerning the mechanical properties of the ancient mortars have been accomplished. In this paper, mortar samples collected from the surviving heritage masonry structures in eastern Sicily were selected to assess their composition. Due to limitations of dimensions, shape and cohesiveness of mortar samples collected from historic buildings, not laboratory test can be applied on the samples. Then, new mortar samples were constructed matching those of historic buildings in order to determine their mechanical properties. Hence, the restored ancient mortar, were tested after 30-60-90 days of curing and finally after 20 years of curing. The data obtained was, then compared each other. To this aim, two series of mortar were performed for a total of 400 samples. The composition of the mortars differs in according to ancient recipes determined in the laboratory by means of the chemical attack of the samples directly taken from historic buildings. The time effects as well as the aggregate (sand) influence were analyzed. To this aim bending, compression and tensile tests were carried out on all the specimens. The data obtained show after 20 years a reduction between 10 and 15% of the compressive strength in mortar studied. All of these data could be very useful for creating compatible mortar recipes for restoration works as well as to define mechanical features of ancient mortar in modeling process.